Regulating a highly concentrated industry: Implications fromDodd-Frank - Alexander Rieber (ZBW - Leibniz Information Centre for Economics, 2021)
Using an international sample of more than 65,000 rating actions by Fitch, Moody's and S&P, we analyze the effect of the Dodd-Frank Act on credit ratings. We document that (i) rating report content changes significantly after Dodd-Frank and (ii) show, by exploiting within firm-quarter variation, that ratings significantly improve after DoddFrank. While ratings are more accurate, updated more frequently, and reflect firm fundamentals more closely, there is no evidence for a decrease in rating stability after Dodd-Frank. Firms, especially constrained firms, benefit and issue more debt after rating agencies' first post Dodd-Frank rating action. For European firms, effects are generally weaker than for U.S. firms
Keywords: G01; G14; G24; G28; 330; Dodd-Frank; Regulation; Cosine Similarity; Credit Rating; Credit Rating Report; Natural Experiment